2018
DOI: 10.1111/sms.13049
|View full text |Cite
|
Sign up to set email alerts
|

The SMS, Phone, and medical Examination sports injury surveillance system is a feasible and valid approach to measuring handball exposure, injury occurrence, and consequences in elite youth sport

Abstract: Current methods of sports injury surveillance are limited by lack of medical validation of self-reported injuries and/or incomplete information about injury consequences beyond time loss from sport. The aims of this study were to (a) evaluate the feasibility of the SMS, Phone, and medical Examination injury surveillance (SPEx) system (b) to evaluate the proportion of injuries and injury consequences reported by SPEx when compared to outcomes from a modified version of the Oslo Sports Trauma Research Centre (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
(71 reference statements)
1
19
1
Order By: Relevance
“…Furthermore, the number of questions asked in the current study (SMS = 2, online survey = 11) was higher than other SMS reported studies. Despite Møller et al recently reporting high compliance to seven SMS messaging questions (96%‐100%), the additional questions in this study together with the differences in the level of prompting (telephone call versus SMS messaging) may have contributed to the lower number of complete of injury records obtained in the current study. Therefore, further development and refinement of the protocol is recommended to determine the optimal number of SMS and online survey questions and additional online survey prompts required.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Furthermore, the number of questions asked in the current study (SMS = 2, online survey = 11) was higher than other SMS reported studies. Despite Møller et al recently reporting high compliance to seven SMS messaging questions (96%‐100%), the additional questions in this study together with the differences in the level of prompting (telephone call versus SMS messaging) may have contributed to the lower number of complete of injury records obtained in the current study. Therefore, further development and refinement of the protocol is recommended to determine the optimal number of SMS and online survey questions and additional online survey prompts required.…”
Section: Discussioncontrasting
confidence: 69%
“…Currently, there is no consensus on the best method for injury surveillance in community sporting populations. The automated method of injury surveillance presented in this study (SMS text messaging and online survey) is an extension of the mixed methods used in previous research; automated SMS messaging with manual follow‐up of injury details by telephone . The method was found to be a feasible and convenient mode of injury surveillance in community sport, with consistent response rates, fast response times, and a moderate to high level of online survey completion.…”
Section: Perspectivementioning
confidence: 83%
See 3 more Smart Citations